The morphological trend in ornithological studies of Professor I.B.Volchanetskiy - Єсілевська, М. А. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 1970)
Professor Ilya Borisovich Volchanetskiy carried out morphological investigations of birds by studying the patterns of color and plumage pattern of similar species and subspecies living in different parts of the area. To this subject he devoted more than half a century since beginning his scientific career in 1927. His last article was published in 1980. According to the results of his research, Gloger’s rule cannot reflect the complexity of the dynamics of the whole plumage of birds. Change of plumage (color lightening or reduction of the drawing) is connected to the historic settlement of a certain taxonomic group of birds. I.B.Volchanetskiy first analyzed the color and other morphological features of a separate taxonomic group of birds in general, comparing them with the range of the species. There have been analyzed: the subfamily Picinae of the family Picidae, family Alaudidae, family Motacillidae, the subspecies of Jay Garrulus glandarius L., Long-tailed Tit Aegithalos caudatus L., and the Spotted Flycatcher Muscicapa striata Pall. Professor I.B.Volchanetskiy has concluded that geographical change of plumage going towards the edges of the area, and only occasionally coincides with climate change. In addition, I.B.Volchanetskiy comes to questions of general biological history of the formation of species and their resettlement. He speculates about the possible origin of the family Alaudidae in the Forest-Steppe.